2023
DOI: 10.4049/jimmunol.2200412
|View full text |Cite
|
Sign up to set email alerts
|

Increased Inflammasome Activation Is Associated with Aging and Chronic Myelomonocytic Leukemia Disease Severity

Abstract: Aging causes chronic low-grade inflammation known as inflamm-aging. It is a risk factor for several chronic disorders, including chronic myelomonocytic leukemia (CMML), a hematological malignancy that is most prevalent in older people. Recent studies suggest a critical role for the NLRP3 (NOD-, LRR- and pyrin domain-containing protein 3) inflammasome in inflamm-aging. However, the mechanisms involved in NLRP3 activation in aging and its involvement in CMML progression are not fully understood. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Compared with those from yHDs, myelomonocytic cells from eHDs overexpressed genes involved in NF-κB signaling and inflammatory response pathways, including IL-1β (Supplemental Fig. 2c,d and Supplemental Table 6), which is consistent with the observation that aged myelomonocytes have increased inflammatory cytokine production 21 . CCUS myelomonocytic cells, which were highly metabolically active, exacerbated inflammatory signaling and overexpressed genes involved in IFN and complement responses (Fig.…”
supporting
confidence: 84%
“…Compared with those from yHDs, myelomonocytic cells from eHDs overexpressed genes involved in NF-κB signaling and inflammatory response pathways, including IL-1β (Supplemental Fig. 2c,d and Supplemental Table 6), which is consistent with the observation that aged myelomonocytes have increased inflammatory cytokine production 21 . CCUS myelomonocytic cells, which were highly metabolically active, exacerbated inflammatory signaling and overexpressed genes involved in IFN and complement responses (Fig.…”
supporting
confidence: 84%
“…Whether elevated AIM2 might play a cooperating role in NLRP3 inflammasome activation in MF monocytes, as previously demonstrated for COVID19 monocytes (51), remains to be determined. In addition to poly(dA:dT), LPS plus nigericin also triggered higher IL-18 production in patients, indicating that other signals acting through NLRP3, such as S100A8/A9 (52), could contribute to NLRP3 inflammasome activation in vivo, as recently shown in monocytes from CMML patients (53). Considering that, besides inflammasomes, dsDNA stimulates several other inflammatory signals (20,21), elevated cfDNA could further contribute to MF inflammation by triggering additional inflammatory cascades.…”
Section: Discussionmentioning
confidence: 56%
“…Recent research indicates that RA may be exacerbated by pyroptosis, a recently identified kind of controlled cell death. The NLRP3 inflammasome triggers caspase-1 during pyroptosis (53,54), which in turn triggers proinflammatory cytokines such IL-18 and interleukin (IL)-1β. Gasdermin D (GSDMD) can be cleaved by caspase-1 and other caspases, and the GSDMD-N-terminal (GSDMD-N) opens pores in the plasma membrane that allow substances like lactate dehydrogenase (LDH) to flow out (55,56).…”
Section: Role Of Gsdmd In Rheumatoid Arthritismentioning
confidence: 99%